2022
DOI: 10.1021/acsenergylett.2c02353
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Reorganization and Additives Synergistically Enable High-Performance Na-Ion Batteries

Abstract: Electrolytes with high and localized salt concentrations have been successfully developed to mitigate parasitic reactions in rechargeable batteries, but at the expense of high cost, high viscosity, and slow kinetics. An alternative electrolyte design concept beyond the current strategies is crucial to reaching practical applications. From salt to solvent, herein, we demonstrate solvent reorganization to develop highly stable dilute phosphate electrolytes (0.16–0.85 M) for Na-ion batteries. This solvent reorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…developed a solvent reorganization and additive synergistic strategy for NaCu 1/9 Ni 2/9 Fe 1/3 Mn 1/3 O 2 (CNFM) ||HC sodium‐ion full cells. [ 84 ] Trifluorotoluene (PhCF 3 ) showed a conjugated benzene ring and a strong negative −CF 3 group, which reinforced the solvation network of electrolytes. With MD simulations, the authors identified some TEP−PhCF 3 aggregates and n ‐(TEP−PhCF 3 ) nanoclusters (Figure 12e), which reduced free TEP molecules and apparently altered the Na + solvation structure.…”
Section: Progress Of Electrolytes For Sibsmentioning
confidence: 99%
See 2 more Smart Citations
“…developed a solvent reorganization and additive synergistic strategy for NaCu 1/9 Ni 2/9 Fe 1/3 Mn 1/3 O 2 (CNFM) ||HC sodium‐ion full cells. [ 84 ] Trifluorotoluene (PhCF 3 ) showed a conjugated benzene ring and a strong negative −CF 3 group, which reinforced the solvation network of electrolytes. With MD simulations, the authors identified some TEP−PhCF 3 aggregates and n ‐(TEP−PhCF 3 ) nanoclusters (Figure 12e), which reduced free TEP molecules and apparently altered the Na + solvation structure.…”
Section: Progress Of Electrolytes For Sibsmentioning
confidence: 99%
“…The functional additives are often sacrificial and intended for modification of SEI/CEI layers during the initial formation cycles. [83,84] They usually exhibit a lower LUMO or a higher HOMO energy level than that of electrolyte components for preferential reduction or oxidation to regulate the formation of electrode/electrolyte interphases (Figure 12a). [85] The most popular additive in SIBs is fluoroethylene carbonate (FEC), which is preferentially reduced to form a stable and robust SEI layer.…”
Section: Electrolyte Additives For Sibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ma et al have developed a high‐performance flame‐retardant phosphate‐based electrolyte with an ultralow concentration (0.16–0.85 M). [ 67 ] By optimizing the ratio of strong and weak solvents, they achieved optimal intermolecular interactions, inducing a stable “solvation cluster” reorganization structure (Figure 6B). This leads to a strengthened solvation network and enhances the electrochemical stability window of the electrolytes on both the negative and positive voltage sides (Figure 6C).…”
Section: Solvation Structures Of Electrolytes and Interfacial Chemist...mentioning
confidence: 99%
“…Reproduced with permission. [ 67 ] Copyright 2022, American Chemical Society. CEI, cathode electrolyte interphase; DME, dimethyl ether; HC, hard carbon; LHCE, localized high‐concentration electrolytes; LiFSI, lithium bis(fluorosulfonyl)imide; LMB, Li‐metal battery; NaFSI, sodium bis(fluorosulfonyl)imide; SEI, solid electrolyte interphase; VC, vinylene carbonate.…”
Section: Solvation Structures Of Electrolytes and Interfacial Chemist...mentioning
confidence: 99%